Enhancing Creative Thinking Character through a Participatory Approach in Secondary School Mathematics Teachers in Jakarta - Flavia Aurelia Hidajat (Transformatif: Jurnal Pengabdian Masyarakat, 2026)
The implementation of this community service aims to improve secondary school mathematics teachers’ creative thinking skills by fostering a more creative, innovative learning process. The method of this community service consists of problem analysis, coordination, and obtaining permission from schools, and socializing materials related to improving character and creative thinking through interactive and innovative approaches. The results of the activity show an increase in teachers’ creative thinking through a participatory approach in this community service program, as reviewed under the aspects of innovation, “flexibility of ideas” and “originality of ideas”. The percentage increase in the innovative character of teachers’ creative thinking is 87.5% (very good criteria). The percentage increase in the “flexibility of ideas” aspect is 81.24% (very good criterion). The percentage increase in the “originality of ideas” criterion is 84.37% (very good). Overall, the community service program aimed at improving teachers’ creative thinking through a participatory approach is running well. This program aligns with character education that is already innovative, effective, and creative. The implication of this community service program is the improvement of creative thinking characteristics in teachers through a participatory approach to being able to create an effective, innovative, and sustainable learning environment.